2011
DOI: 10.1016/j.eurpolymj.2011.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Polypeptide grafted hyaluronan: A self-assembling comb-branched polymer constructed from biological components

Abstract: Rheological evidence is provided demonstrating that covalent grafting of monodisperse isotactic poly(L-leucine) branches onto linear hyaluronan (HA) polysaccharide chains yields comb-branched HA chains that self-assemble into long-lived physical networks in aqueous solutions driven by hydrophobic interactions between poly(L-leucine) chains. This is in stark contrast to native (unmodified) HA solutions which exhibit no tendency to form long-lived physical networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Below this crossover frequency, i.e., in the terminal regime, G ″ > G ′ (implying that the behavior is viscous at longer timescales); conversely, above this frequency, G ′ > G ″ (implying that the behavior is elastic at shorter timescales). Such crossing of G ′ and G ″ is the characteristic of polymer chains exhibiting molecular association into networklike structures, where the crossover frequency may be identified with the average network lifetime. , Physically this means that at timescales over which G ″ > G ′, polymer chains have sufficient time to escape from the constraints of surrounding chains, and thus show viscous behavior, while at shorter timescales, the chains are localized by surrounding chains, and the material exhibits elastic behavior. A similar viscoelastic response is observed in “entangled” polymer solutions, along with the same trend in the crossover frequency with polymer concentration. , …”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Below this crossover frequency, i.e., in the terminal regime, G ″ > G ′ (implying that the behavior is viscous at longer timescales); conversely, above this frequency, G ′ > G ″ (implying that the behavior is elastic at shorter timescales). Such crossing of G ′ and G ″ is the characteristic of polymer chains exhibiting molecular association into networklike structures, where the crossover frequency may be identified with the average network lifetime. , Physically this means that at timescales over which G ″ > G ′, polymer chains have sufficient time to escape from the constraints of surrounding chains, and thus show viscous behavior, while at shorter timescales, the chains are localized by surrounding chains, and the material exhibits elastic behavior. A similar viscoelastic response is observed in “entangled” polymer solutions, along with the same trend in the crossover frequency with polymer concentration. , …”
Section: Resultssupporting
confidence: 74%
“…In certain biomedical applications of the polymers considered in the present work such as vehicles for gene therapy, nanoparticle drug delivery, tissue engineering, and as a material for boosting the viscoelastic properties of the synovial fluid of the joints of patients with arthritis, the molecules are “hydrophobically modified” by grafting alkanes and other relatively hydrophobic side groups (e.g., proteins) to these polymers. Kandadai et al investigated the rheology of HA modified by isotactic poly­(L-leucine) and found that its behavior indicated a weak-gel rheological response. This effect was interpreted in terms of the supramolecular polymer assembly of the hydrophobically modified chains, similarly to our interpretation of the rheological properties of aggrecan–HA solutions.…”
Section: Resultsmentioning
confidence: 99%
“…However, its crystallization has an impact on its degradation rate and affects its application. The architectural effect on properties of polymers has been studied by some groups, , including the architecture effect on the crystallization behavior of polymers containing PCL. For example, Choi et al studied the crystallization of three hyperbranched PCLs as well as their linear counterparts with different lengths of homologous PCL segments and different numbers of branching points but similar molecular weights, and they found that the lengths of the linear backbone segments have a positive effect on the crystallization while the numbers of branching points bring opposite effect. Therefore, we further studied the crystallization of unfractionated HB-(PS 18 - b -PCL 28 ) n with different weight-average molar masses by POM and DSC measurements.…”
Section: Resultsmentioning
confidence: 99%
“…We note that in certain biomedical applications (gene therapy, nanoparticle drug delivery, tissue engineering, and as a material for boosting the viscoelastic properties of the synovial fluid of the joints of patients with arthritis), certain polymers considered in the present work (e.g., HA) have been “hydrophobically modified” by grafting alkane chains, and other relatively hydrophobic side groups (e.g., peptides) onto these molecules, which evidently enhances the formation of materials in a weak gel state. For example, Kandadai et al [ 90 ] investigated the rheology of HA modified with isotactic poly(L‐leucine) and found a rheological response consistent with weak gel formation. This viscoelastic response was interpreted in terms of the supramolecular assembly of the hydrophobically modified chains, similarly to our interpretation of the rheological properties of aggrecan−HA solutions.…”
Section: Biomedical Implications Of the Weak Gel State Of Materialsmentioning
confidence: 99%